Comportamento de cátions percolados oriundos da aplicação de água residuária de suinocultura em solo cultivado com milho - Zanuzo, Lusiani (2007)
The objective of this work was evaluated the cation´s leaching corn planted and irrigated with swine waste water in lysimeters. The factors and levels of treatments were: four levels of with swine wastewater (112.5, 225.0, 337.5 and 450.0 m3 ha-1), two levels of chemical fertilization (50% and 75% of nitrogen recommend) and three repetitions. The time after sowing was considered analysis factor to evaluate the time effects accumulation of cations in soil. The irrigation was realized switching water and wastewater in each period of 15 days. The lysimeters was built with fiber boxes, capacity of 1 m3, 1.6 m of diameter, spacing of 0,4 x 0,5 m and 1,2 m of depth. The statistical analysis used was split-plot. The leaching´s concentrations were larger for the chemical elements in the following order: Na+ > K+ > Ca2+ > Mg2+. In general, the factor swine wastewater produced proportional larger concentrations in the leaching of Na+. The chemical fertilization factor influenced in the largest concentrations of the K+ leaching. The time after sowing influenced in the largest concentrations of Ca2+ and Mg2+ in the soil and of Na+ leaching.